2019
DOI: 10.1016/j.jaut.2018.08.002
|View full text |Cite|
|
Sign up to set email alerts
|

Fingolimod modulates T cell phenotype and regulatory T cell plasticity in vivo

Abstract: Fingolimod is an approved therapeutic option for patients with relapsing-remitting multiple sclerosis that primarily functions by sequestering T cells in lymph nodes inhibiting their egress to the central nervous system. However, recent data suggests that Fingolimod may also directly affect the immune cell function. Here we examined the in vivo effects of Fingolimod in modulating the phenotype and function of T cell and Foxp3 regulatory T cell populations in patients with multiple sclerosis under Fingolimod tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 72 publications
4
33
0
Order By: Relevance
“…The analysis of fingolimod effects on T cells during 12 months of treatment also evidenced a modulation of the phenotype of Th cells and Treg cells. Effector Th cells showed a decrease of IL-17 and IFN-γ and an increase of TGF-β and IL-10 production together with the expression of exhaustion markers such as programmed death 1 (PD-1) and T-cell immunoglobulin and mucin-domain containing-3 (TIM3) [189]. Moreover, the suppressive functions of Treg in fingolimod-treated RRMS patients were also upregulated, thus evidencing an additional role of fingolimod in restoring peripheral tolerance besides the retention of T lymphocytes in lymph nodes [189].…”
Section: T Cell Targeting Therapymentioning
confidence: 99%
“…The analysis of fingolimod effects on T cells during 12 months of treatment also evidenced a modulation of the phenotype of Th cells and Treg cells. Effector Th cells showed a decrease of IL-17 and IFN-γ and an increase of TGF-β and IL-10 production together with the expression of exhaustion markers such as programmed death 1 (PD-1) and T-cell immunoglobulin and mucin-domain containing-3 (TIM3) [189]. Moreover, the suppressive functions of Treg in fingolimod-treated RRMS patients were also upregulated, thus evidencing an additional role of fingolimod in restoring peripheral tolerance besides the retention of T lymphocytes in lymph nodes [189].…”
Section: T Cell Targeting Therapymentioning
confidence: 99%
“…The reduction in the absolute number of IL-17 + T cells in the peripheral blood might be due to sequestration of cells in the lymph nodes or due to immunomodulatory effects of fingolimod. [36,37,43,44] Reduction of central memory Th17 cells in the peripheral blood after fingolimod treatment have been reported previously although others have shown a subset of patients that had increased Th17 cells. [37,43] Fingolimod may also reduce polarization to Th17 by reducing Th17-polarizing cytokine production by dendritic cells [36] or suppressing IL-17 production by CD4 + T cells.…”
Section: Discussionmentioning
confidence: 62%
“…Fingolimod also has immunomodulatory properties particularly on Th17 and Treg cells. [33][34][35][36] In this study we compared Th17 cell number, and Th17associated cytokines in the peripheral blood of untreated RRMS patients to those treated with fingolimod via flow cytometry-based assays. Previous studies have shown a reduction in IL-17 producing cells in the peripheral blood after Fingolimod treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same study it was also shown that in patients undergoing treatment with fingolimod the phenotypic conversion from naïve Treg cells to effector T cells occurs with greater frequency. Fingolimod also affects Treg plasticity by reducing the expression of T-bet and of IFNγ and by enhancing expression of Tim-3, a marker associated with superior suppressor capacity (212). In general, these studies show that Treg function is increased following treatment with fingolimod.…”
Section: Effects Of Immunomodulatory Drugs For Ms On Tregsmentioning
confidence: 73%